YOUNG PEOPLE SAY NO TO DRUGS - Normamatov Abdukarim Abdunabiyevich (Journals Park Publishing, 2023)
In this article, the religious essence of Islam in our society, its inter-religious aphorisms and its extremely beautiful qualities in the human world are highlighted with evidence.
Keywords: Religious tolerance, Social networks, Uzbekistan and world religious ideas, Islamic religious virtues, religious fanatics